(untitled) (Journal of Geography and Environmental Management, 2016)
This article is devoted to system of the taxation of lands of agricultural purpose. Increase of a land tax on this category of lands is in the long term supposed. In this regard, the author studied experience of the taxation of lands in foreign countries and on their basis offers on technique change definitions of land payments are given. Taking into account offers expected calculations of a land tax and a rent of agricultural producers are made.